The Predicament of Writing Political History: The Challenge of the Tacit. (March 2016) - Jones, Adrian
Abstract : Political histories composed by contemporaries (or near contemporaries) are affected by the predicament of confronting the tacit in a past. Three case studies of famous writers of histories of politics in their own times are used to suggest an additional epistemology for political history which relies rather less on representations than has been common since the "Linguistic Turn" privileged the propositional thrall of discourses. My extra element attends to the tacit in human lives: affects and effects in context of the lived‐in and lived‐around of politics. My three case studies suggest that histories of politics and policies by contemporaries and near‐contemporaries do not simply amount to a re‐representation (broadly defined) of past representations (broadly defined). A wide angle is adopted; three case studies treat renowned political historians, ancient, mediæval and modern: Procopius in the mid‐sixth, Commynes in the late‐fifteenth, and A.J.P. Taylor in the mid‐twentieth centuries. Each of these "great" historians of politics was driven to discount the lived‐out‐loud of politics they narrated in, or close to, their own times. The predicament and the response is more general, I believe: all historians of politics have to try to situate and narrate things once taken‐for‐granted. That predicament prompted each of my three — and still prompts historians — to have to transcend "representationalism". The three cases show how and why history writing about politics also needs to attend to the habitual and tacit in a past, the ubiquitous things seldom represented. A controversial foundation for such an "extra" epistemology is then suggested: Dasein, the being‐of‐being, a key concept of Martin Heidegger's. The writing of political history by contemporaries (or near‐contemporaries) is then conceived as also a (ethnography‐like) study of past life‐worlds‐in‐being. This extra foundation for (very‐old and still current!) writing practices about power and politics emphasises metonyms over metaphors. Surprises discerned from contexts are emphasised over propositions peddled in representations. The metonyms disclosed by my three case studies, which I think apply in most writing about politics by contemporaries or near contemporaries, had to be inferred from contexts, rather than read as discourses. The tacit is elicited by contemporaries from (1) records and recollects of predicaments and situations, and from (2) reading actions as texts. Histories of politics are really about things people once felt and did, more than what they said, in their there‐and‐then.